Efficient Oxidation and Destabilization of Zn(Cys)4 Zinc Fingers by Singlet Oxygen1. Issue 35 (7th July 2014) - Lebrun, Vincent; Tron, Arnaud; Scarpantonio, Luca; Lebrun, Colette; Ravanat, Jean‐Luc; Latour, Jean‐Marc; McClenaghan, Nathan D.; Sénèque, Olivier
Abstract Singlet oxygen (1O2) plays an important role in oxidative stress in all types of organisms, most of them being able to mount a defense against this oxidant. Recently, zinc finger proteins have been proposed to be involved in its cellular detection but the molecular basis of this process still remains unknown. We have studied the reactivity of a Zn(Cys)4 zinc finger with 1O2 by combinations of spectroscopic and analytical techniques, focusing on the products formed and the kinetics of the reaction. We report that the cysteines of this zinc finger are oxidized to sulfinates by 1O2. The reaction of the ZnS4 core with 1O2 is very fast and efficient with almost no physical quenching of 1O2. A drastic (ca. five orders of magnitude) decrease of the Zn2+ binding constant was observed upon oxidation. This suggests that the Zn(Cys)4 zinc finger proteins would release their Zn2+ ion and unfold upon reaction with 1O2 under cellular conditions and that zinc finger sites are likely targets for 1O2.